Calculation of Land Water Balance and Its Utilization for Determining the Growing Season in the Pulau-Pulau Aru District, Aru Islands Regency, Maluku Province - Elia L Madubun; Semuel Laimeheriwa; Merson Panggua (JURNAL BUDIDAYA PERTANIAN, 2022)
There are various methods that can be used to determine the growing season in an area; one of them is through the calculation of the land water balance. This study aimed to determine the presence of groundwater and determine the planting season in the Pulau-Pulau Aru Sub-District. In this study, the calculation of the regional average rainfall used monthly time series rainfall data for 30 years of observation (1991–2020). The calculation of land water balance used the ThornthwaiteMather method, and the determination of the growing season based on the values of soil water content at optimum conditions and the ratio between rainfalls and potential evapotranspiration. The results showed that the optimum soil water content for plants under conditions of 75% chance of rainfall lasted for 7 months (December to June), which was 2 months shorter than normal. The length of growing season with a 75% chance of rainfall lasted for 7 months (December to June), 2 months shorter than the growing season under normal rainfall conditions.